Estimating North Korea's nuclear capabilities: Insights from a study on tritium production in a 5MWe graphite-moderated reactor - Yang, Sungmin; Lee, Manseok; Ko, Danwoo; Heo, Gyunyoung; Kang, Changwoo; Woo, Seung Min (Nuclear engineering and technology, 2024)
This study explores the potential for tritium production in North Korea's 5MWe graphite-moderated reactor, a facility primarily associated with nuclear weapons material production. While existing research on these reactors has largely centered on plutonium, our focus shifts to tritium, a crucial element in boosted fission bombs. Utilizing the MCNP6 code for simulations, the results estimate that North Korea can possibly produce approximately 7–12 g of tritium annually. This translates to the potential production of 1–3 boosted fission bombs each year. By incorporating tritium production into assessments of North Korea's nuclear capabilities, our methodology provides insights into the dynamics of the country's nuclear force, revealing a more diversified and complex composition than previously assumed. The findings significantly aid policymakers, regulatory bodies, and researchers in comprehending potential proliferation risks associated with graphite-moderated reactors and in developing strategies to address the nuclear threat emanating from North Korea.